Russian Federation : 2010 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Russian economy has improved after the recession, but recovery is fragile. Executive Directors appreciated the pre-crisis policy of taxing and saving oil revenues in a stabilization fund, which had created significant space for fiscal expansion, monetary easing, and extraordinary liquidity support to the banking system while helping to prevent an abrupt ruble depreciation. Directors agreed that the main challenges will be to implement medium-term fiscal consolidation, mitigate pressures for real appreciation and inflation, restore the health of the banking system, and improve the investment climate through ambitious structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet